Research on Legal Protection of Consumers’ Personal Information From the Perspective of Public Interest Litigation (Asian Journal of Social Science Studies, 2022)
In the era of big data, consumers’ personal information security is facing severe challenges and risks. Therefore, it is urgent and important to strengthen the protection of consumers’ personal information. In the personal information leakage incident of consumers, the victims are unspecified groups, and the number of consumers who have suffered losses and the actual losses of ordinary consumers is uncertain. By filing consumer civil public interest litigation, consumers can be effectively encouraged to defend their rights through litigation, which increases the cost of offense and avails the prevention of illegal behaviors. However, there are still many problems in public interest litigation of consumers’ personal information protection. Firstly, it is difficult to distinguish the subject of infringement and its internal responsibility allocation. Secondly, the level of evidence collection means of procuratorial organs can’t match the needs of the investigation, which disadvantages prosecutors compared with the powerful objects of evidence collection. Thirdly, the problems of jurisdiction confirmation and low efficiency on the referral of jurisdiction have not been solved. Fourthly, the overlapping of laws has caused the judge’s discretion to be too wide. Fifthly, the standard of remedies for infringement is unclear. Based on those above, this paper puts forward some suggestions on public interest litigation of consumers’ personal information from five aspects: positioning the subject of infringement, standardizing jurisdiction, strengthening investigation and evidence collection, perfecting legal responsibility and clarifying the application of law.